Physicochemical structure characteristics and combustion kinetics of low-rank coal by hydrothermal carbonization. (1st January 2022) - Zhang, Nan; Wang, Guangwei; Yu, Chunmei; Zhang, Jianliang; Dang, Han; Zhang, Cuiliu; Ning, Xiaojun; Wang, Chuan
Abstract: To improve the quality of low-rank coal to meet requirements of blast furnace, hydrothermal carbonization (HTC) was used to treat low-rank coal to analyze the change rule of physicochemical properties, structural characteristics and combustion performance. Results showed that with an increase in HTC temperature, the calorific value increased from 25.29 to 28.85 MJ/kg. The ash content dropped from 11.74 of raw coal to 7.16. In addition, the atomic ratio of O/C and H/C decreased from 0.21 to 0.79 to 0.12 and 0.56, respectively. Structural analysis revealed that the aromaticity was improved, but the aliphatic carbon content reduced. The coal property was closer to bituminous coal with medium metamorphic degree. The carbon ordering degree also increased, indicating an increase in energy density. Combustion and kinetic analyses showed that with an increase in HTC temperature, compared with raw coal, the combustion curve first moved to the low temperature zone and then gradually shifted to the high temperature zone. Furthermore, the comprehensive combustion characteristics were improved. And the burnout time, which had a certain relationship with ash removal, was shortened. The average reaction activation energies all showed a trend of increasing first and then decreasing, with a range between 114.2 and 147.6 kJ/mol. Highlights: The HTC method was used to treatment low-rank coal to prepare blast furnace injection fuel. Physicochemical properties and combustion performance of low-rank coal after HTC were studied. The degree of aromatization and graphitization of low-rank coal increased after HTC treatment. Comprehensive combustion characteristics of hydrochar were considerably improved.